Edukasi Hukum Terhadap Risiko Penyalahgunaan Kuasa Dalam Pembuatan Akta - Khairani, Intan (Jurnal Pengabdian West Science, 2025)
In notarial practice, trust in third parties is often the root of legal problems, especially in making deeds. One case found during an internship at a notary's office showed an abuse of trust by a party who was given the authority to take care of making deeds, but instead misused funds that should have been paid to the notary. As a form of community service, legal counseling activities were carried out to the surrounding community regarding the importance of making a written power of attorney, understanding the legal flow of making deeds, and the legal risks if misuse occurs. The activity methods were in the form of case observation, preparation of legal materials, and direct counseling. The results showed that the community was quite enthusiastic and aware of the importance of verification and caution in appointing a power of attorney. This legal education is expected to be a preventive effort to avoid similar problems in the future.